Kategori Leksikal Idiom dalam Bahasa Lampung - Sulistianah Sulistianah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This research aimed to describe lexical category (word class) and meaning of idiom in Lampung language. Descriptive qualitative was used in this research. The findings showed that idiom in Lampung language could be in form of complex word, word combination, and idiomatic expression. There were two idioms in complex word namely penghenguk and pedatong . Idiom in form of word combination could be a combination of noun+noun, noun+adjective, noun+verb, verb+adjective and verb+verb. The conclusion of the research based on verb semantic attitude that was used in form of words combination like state verb and action verb Keywords: Lexical, idiom, Lampung language.